キョクイキ ニオケル テレサイエンス ギジュツ ノ ゲンジョウ ト テンボウ ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 金尾, 政紀; カナオ, マサキ; Kanao, Masaki (2004)
P(論文) 平成15年11月17日に国立極地研究所講堂にて,「極域におけるテレサイエンス技術の現状と展望に関する研究小集会」を,所内外の参加者計30名で開催した.本集会では,将来の南極における機動観測・無人観測点展開のための基盤技術として,自然エネルギーを利用した電源開発,低消費電力の観測器械の開発,また航空機からの投下設置式観測器械,さらに衛星通信・無線通信利用など,分野を越えた幅広い議論を行うことを目的とした.会合は,1)極域科学に関係する様々な研究分野に応用できる基盤技術に関する発表,2)実際の南極大陸への応用と関連する将来の国際共同研究の紹介,3)今後の取り組み方等についての総合討論,に分けて行われた.本集会により,実際の観測例や現在の開発状況について情報提供を行い,地球環境変動を高緯度地域から視ることの重要性について再認識を行った.また,将来の南極における機動観測・無人観測点展開のための基本的な開発思想についても意見交換を行い,お互いに関連する技術について分野を越えた議論をした.さらに,2007-2008年の国際極年(International Polar Year: IPY)にも関連して,南極大陸内部で航空機を用いた大規模なアレイ観測計画等への我が国の取り組みについて,参加者の共通理解を得た. A workshop on Present status and future plans for telescience techniques in polar regions" was held on 17th November 2004, at the National Institute of Polar Research with 30 participants. The purposes of this workshop were to discuss several technical aspects of telescience observations in polar regions, such as of the utilization of natural energy, developments of low-power consumption instruments, development of a shooting-type acquisition-system from airborne platforms, and telecommunication techniques using satellite and/or radio transmissions. The workshop was divided into the following three sessions. 1) Basic technique for telescience observations by individual science branches. 2) Application to field observations in the Antarctic, in particular operations of the Japanese Antarctic Research Expedition (JARE), together with future international cooperative programs. 3) Discussion about further approaches and future plans. The principal achievements of this workshop were to point out the significance of polar studies to global Earth science, in particular, for insight into the Earth's environmental changes as viewed from high latitude remote stations. Moreover, we had fruitful discussions about the newest information and future plans for telescience technology, remote observation systems, and methodology for data communications. Finally, we reached agreements on the international collaborative program, with respect to contributions to the ...